Official Language Minority Communities, Machine Translation, and Translator Education: Reflections on the Status Quo and Considerations for the Future - Bowker, Lynne (TTR, 2008)
AbstractOwing largely to budgetary pressures, official language minority communities in Canada have a great number of unmet translation needs. The use of machine translation presents the possibility of a cost-effective solution, but only if members of this community are willing to accept this form of translation. This paper reports on an experiment whereby members of one official language minority community in Canada—the Fransaskois—were surveyed to determine their level of acceptance of machine translation. Results show that while many Fransaskois are quite favourable to the possibility of using post-edited machine translation, those who are also language professionals are extremely opposed to the use of any form of machine translation. This finding prompts a reflection on whether the way in which translators are trained in the use of technology could be an underlying factor in their reaction to machine translation use, which in turn leads to a proposal for a new approach to integrating technology more fully into translator training programs.